(untitled) (Bangladesh Journal of Botany, 2022)
Effects of eight different potting media compositions on growth and flowering traits of Calendula was studied. Among different media compositions, T5 have positive effect on root length (18.33 cm), number of leaves (62.77) and number of branches (9.12) per plant while T3 was found to be best for root spread (14.10 cm) and plant spread (22.67 cm). Calendula plants raised in T5 exhibited maximum (6.10 cm) flower diameter and flower bud diameter (1.40 cm), took minimum days (66.39) for flower bud initiation and also for flower bud opening (74 days). Maximum number of flower buds and flowers per plant were recorded in T2. The growth and flowering of Calendula was found superior in media composition of vermicompost and cocopeat. Bangladesh J. Bot. 51(3): 417-424, 2022 (September)